UPAYA TIONGKOK MEMENUHI PERJANJIAN EKONOMI DAN PERDAGANGAN FASE-1 DENGAN AS MELALUI PENGAMANDEMENAN HUKUM PATEN TIONGKOK - Jeko Spastyono (2020)
The problem of the inadequate legal quality of Chinese intellectual property laws is like malignant cancer for the US, which is getting bigger with time and increasing economic losses for the US. And the phase 1 economic and trade agreement between the US and China is an attempt to resolve this issue. Where the purpose of this thesis is to see how China's actual efforts are to fulfil this agreement through safeguarding its country's patent law. Where this research will be analyzed using international agreements related to the concept of good faith and bad faith to see whether the fulfilment of the agreement is carried out properly or not by China. And the results of the study found that even though China carried out fulfillments that showed good faith by not violating the phase-1 economic and trade agreement with the US and also fulfilling several articles of this agreement. However, the results of this study also found that China's fulfilment efforts also show bad faith by not fulfilling what should be done, where this bad faith is found in the improvement of articles related to technology transfer, exclusive rights, enforcement rights, and deterrents from China patent law.